2020
DOI: 10.3389/fneur.2020.00538
|View full text |Cite
|
Sign up to set email alerts
|

Novel Treatments in Myasthenia Gravis

Abstract: Myasthenia gravis (MG) is the prototypical autoimmune disorder caused by specific autoantibodies at the neuromuscular junction. Broad-based immunotherapies, such as corticosteroids, azathioprine, mycophenolate, tacrolimus, and cyclosporine, have been effective in controlling symptoms of myasthenia. While being effective in a majority of MG patients many of these immunosuppressive agents are associated with long-term side effects, often intolerable for patients, and take several months to be effective. With adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 97 publications
0
83
0
2
Order By: Relevance
“…Insurance coverage and formulary issues may have influenced neurologists' reported choices of tests and treatments. Because the range of treatment options for MG is broadening, it is likely that cost will become an even larger factor in treatment decisions (5). Survey results showed that current treatment decision-making often results in a higher cost burden for the patient and health care system: IVIg/SCIg was the most commonly reported second-line therapy for patients with AChR antibodypositive gMG after an NSIST failed to control their symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insurance coverage and formulary issues may have influenced neurologists' reported choices of tests and treatments. Because the range of treatment options for MG is broadening, it is likely that cost will become an even larger factor in treatment decisions (5). Survey results showed that current treatment decision-making often results in a higher cost burden for the patient and health care system: IVIg/SCIg was the most commonly reported second-line therapy for patients with AChR antibodypositive gMG after an NSIST failed to control their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There are broadly accepted therapies for MG, although often with low levels of evidence to support their use (5) and, until recently, there were no international recommendations to guide care for MG. As treatment options continued to expand, improved strategies for managing this heterogeneous disease became necessary (6). Accordingly, a 15-member international task force was convened in 2013 by the Myasthenia Gravis Foundation of America (MGFA) to address this unmet need.…”
Section: Introductionmentioning
confidence: 99%
“…6 Conventional therapies for the treatment of myasthenia gravis include cholinesterase inhibitors (e.g., pyridostigmine), which increase the amount of acetylcholine available at the neuromuscular junction, corticosteroids (e.g., prednisone), which are immunosuppressants, thymectomy, where the thymus gland is removed to stop the production of autoantibodies, and other immunomodulatory therapies (e.g., azathioprine, cyclosporine, IV immunoglobulin, and plasma exchange). [7][8][9] The goal of these therapies is to achieve stable disease where patients experience limited symptoms (i.e., minimal manifestation status). 10 Although many patients experience success with these approaches, approximately 10% of those with generalized myasthenia gravis are refractory to or are unable to tolerate conventional therapies.…”
Section: Context and Policy Issuesmentioning
confidence: 99%
“…Rituximab was very effective in the few OMG subjects treated so far (99,100) and, although evidence is scarce, may be considered in refractory disease. Lastly, OMG patients were not included in RCTs investigating novel therapeutic options based on complement inhibition or competition with IgG for the Fc neonatal receptor (101).…”
Section: Therapeutic Optionsmentioning
confidence: 99%